Construction Industry Payment and Adjudication Act (CIPAA) Remedying Payment Issues: CIDB G7 Contractor's Perspective - Nik Din, Nik Mohd Dhiyafullah; Ismail, Zulhabri (Journal of Technology Management and Business, 2014)
Payment defaults remain chronic and prevalent issues that affecting the entire delivery chain of construction industry. For that particular reason, Government of Malaysia have embarked serious afford to reduce payment default issues by enacting Construction Industry Payment and Adjudication Act (CIPAA) in 2012. Acknowledging the fact that CIPAA is relatively new to the industry, the possibility of industry's key players to be lack of information and awareness about CIPAA is greater. Therefore, this research aims to explore and reveal remedies offered via CIPAA as well as the awareness and expectation of CIDB G7 contractors towards CIPAA. Hence, the research objectives are to identify pertinent features of CIPAA in remedying payment default issues, to investigate the perceptions and expectations of CIDB G7 contractors towards CIPAA in addressing payment default issues and to examine the potential implications and limitations of such Act towards current construction industry practices. This research has adopted mixed methods of questionnaire survey and semi-structured interviews to CIDB G7 Contractors in Klang Valley area. The research suggested that the most pertinent feature of CIPAA from contractors' point of view is to streamlining payment procedures for construction works. Apart from that, research also revealed that contractors are optimistic that CIPAA will be able to provide legal remedy to non-payment and improve the delivery system in construction industry. Although CIPAA will be the platform for resolving payment disputes by means of adjudication decision and establish payment process, procedures and timeframes, it is anticipated that CIPAA is depending on the competency and integrity of the adjudicators. In conclusion, it is aimed that the construction industry can be benefited from the enactment of CIPAA. Thus, the industry as a whole must collaborate and focus on their synergies to promote effective implementation of CIPAA.